Pro-Poor Tax reforms, with an Application to Mexico - Duclos, Jean-Yves; Makdissi, Paul; Araar, Abdelkrim (Université d'Ottawa | University of Ottawa, 2009)
This paper proposes a new methodology to test for whether indirect tax reforms are pro-poor. The methodology extends stochastic dominance techniques and enables identifying tax reforms that will necessarily be deemed absolutely or relatively pro-poor by a wide spectrum of poverty analysts. The statistical properties of the various estimators are also derived in order to make the method implementable using survey data. The methodology is used to assess the pro-poorness of possible reforms to Mexico’s indirect tax system. This leads to the identification of several possible pro-poor tax reforms in that country. / Cet article propose une nouvelle méthode permettant de déterminer si une réforme de la fiscalité indirecte est pro-pauvre. Cette méthode adapte des techniques de dominance stochastique permettant ainsi d’identifier les réformes fiscales qui seront considérées absolument ou relativement pro-pauvre par un large éventail d’analystes de la pauvreté. Les propriétés statistiques des différents estimateurs sont dérivées afin de rendre la méthode applicable à des données d’enquêtes. La méthode est utilisée afin d’identifier plusieurs réformes de la fiscalité indirecte mexicaine qui serait pro-pauvres.
Keywords: Stochastic dominance; pro-poor changes; tax reforms; indirect taxation; poverty; Mexico; Dominance stochastique; changements pro-pauvre; re?formes fiscales; taxation indirecte; pauvrete?; Mexique